THE DEVELOPMENT OF ARTISTS’ CREATIVITY BASED ON THE METHOD OF “INTUITIVE AESTHETICS”: RESULTS OF EN PLEIN AIRS (LITHUANIA, VILNIUS, 2018) - Balte-Balciuniene, Rasa; Kharitonova, Tatiana; Chekmaryova, Marina (PEOPLE: International Journal of Social Sciences, 2020)
The article is devoted to the problem of development of creativity of modern painters in Lithuania. Development of painter’s personality helping to step of from the stereotypes of creativity is one of the most significant challenges of psychology of modern art. Psychologists conduct large number of studies, make publications on problems of visual communication, psychodynamic theories of personality, psychological characteristics of artists, but not enough attention is being paid to the development of methods that would help to deal with the issue of developing creativity. Impact of the “Intuitive Aesthetics” method as a way to step out from the stereotypes that hinder creativity was researched in the project for Lithuanian painters. 40 well-known Lithuanian painters took part in two En Plein Airs held in Vilnius (Lithuania) in 2018. The “Intuitive Aesthetics” method included four interactions:1) seminar on art psychology, mindfulness and embodyment; 2) practice for developing skills of reflection; 3) live painting; 4) independent painting. The article presents the results of the research showing how the “Intuitive Aesthetics” method helped to change stereotypes of creativity of painters. Method “Intuitive Aesthetics” can be considered as psychological authentication counselling of the painters that help them to step out from the stereotypes that hinder their creativity.